Practices of interfaith moderation on Punjungan tradition in Kecis Village - Elsha Pipit Nathalia; Harto Wicaksono (Universitas Muhammadiyah Malang, 2025)
The residents of Kecis Village demonstrate their commitment to both Christianity and Islam by fostering interfaith tolerance. The practice of the punjungan tradition, observed during Christmas and Eid, facilitates moderation in the interfaith community. Punjungan represents an expression of goodwill towards individuals of different faiths, marked by the sharing of food to commemorate religious holidays. This study examines the model of interfaith moderation cultivated through the punjungan tradition within the framework of religious moderation and Bourdieu's social practice theory. Employing a qualitative research methodology, this study focuses on ethnographic analysis through interviews, observations, and a literature review. The findings indicate that punjungan, as a symbol of communal affection, effectively rationalizes the practice of the punjungan tradition, thereby promoting tolerance and harmony among interfaith communities in Yogyakarta. The significance and rationalization of the punjungan tradition serve as mechanisms for establishing habitual moderation through the process of interfaith community habituation. The integration of religious moderation concepts within the punjungan tradition is conducted systematically, offering a model to mitigate the risk of disintegration within interfaith communities. Masyarakat Desa Kecis menganut agama Kristen dan Islam dengan menjaga toleransi antar lintas agama. Hadirnya praktik tradisi punjungan yang dilakukan pada Natal dan Idulfitri menciptakan moderasi masyarakat lintas agama. Punjungan adalah bentuk tali kasih kepada sesama berbeda keyakinan untuk mengabarkan hari besar agama dengan memberikan makanan. Penelitian ini bertujuan menganalisis model praktik moderasi lintas agama yang terhabituasi tradisi punjungan dalam konsep moderasi beragama dan teori praktik sosial Bourdieu. Metode penelitian yang digunakan adalah kualitatif, berfokus pada studi etnografi melalui wawancara, observasi, dan studi kepustakaan. Hasil penelitian menunjukkan, punjungan sebagai bentuk tali kasih mampu menciptakan rasionalisasi praktik tradisi punjungan, toleransi dan harmonisasi masyarakat lintas agama. Melalui pemaknaan dan rasionalisasi praktik tradisi punjungan menjadi alat untuk menciptakan moderasi yang terhabituasi melalui proses habituasi masyarakat lintas agama. Proses habituasi konsep moderasi beragama dilakukan secara terintegrasi dalam proses praktik tradisi punjungan, sehingga dapat menjadi model untuk mencegah ancaman disintegrasi masyarakat lintas agama.